The Latin American countries and the New International Economic Order - Pedro Malan (CEPAL Review, 1980)
As is well known by now, the so-called North-South agenda is made up of a whole array of political and economic issues: the presently changing patterns of trade, old and new trade restrictions, the implications of foreign investment, the volume and burden of foreign debt, the yet to be designed future international monetary system, the controversial commodity price stabilization schemes, the frightening poverty of the Fourth World, and so on. It is obvious that these issues will remain on the agenda —political and economic— for many years to come. This is not the time to present yet another survey of the present state of frustration with respect to the progress achieved so far in several of the topics listed above.